MoS2/pentacene hybrid complementary inverter based photodetector with amplified voltage–output. (19th October 2020) - Liu, Fengjing; Zhang, Yiwei; Wang, Jiawei; Chen, Yiyi; Wang, Liang; Wang, Gongtang; Dong, Ji; Jiang, Chao
Abstract: A sensitive photodetection based on a novel hybrid CMOS inverter has been demonstrated. Unlike common photo-current type photodetectors, which convert optical signals to current, the CMOS inverter realizes voltage–output, overcoming the difficulty to monitor current signal in the range of nA . The hybrid CMOS logic inverter employs n-channel MoS2 nanosheet/perovskite heterojunction FET and p-channel organic pentacene FET in a planar architecture. In order to obtain high performance, we adopt the interdigital electrodes for the pentacene FET to enhance the current density of the p-channel, and stack perovskite on the MoS2 channel to modify the threshold voltage of the n-channel. As a result, a CMOS inverter with a voltage gain of more than ten is obtained. When VIN is around the transition voltage (−38 V), the inverter can obtain stable optical detection signal, the VOUT changes from 6 V in dark to 1 V under 633 nm light exposure. This finding indicates the potential to fabricate visible light detecting devices with voltage–output based on the inverter and may be further applicable for a photo-logic circuit.